Works Councils and Learning: On the Dynamic Dimension of Codetermination - Uwe Jirjahn; Jens Mohrenweiser; Uschi Backes-Gellner (Universität Trier, Fachbereich IV – Volkswirtschaftslehre, 2010)
This study provides the first econometric analysis on the dynamic dimension of establishment-level codetermination in Germany. We hypothesize that learning implies a change in the nature and scope of codetermination over time. Using unique data from small- and medium-sized establishments, our empirical analysis provides strong evidence that learning indeed plays a crucial role in the functioning of works councils. First, the probability of an adversarial relationship between management and works council is decreasing in the age of the council. Second, the council's age is positively associated with the probability that the council has an influence even on decisions where it has no legal powers. Third, establishment output is increasing in the age of the council. Fourth, the quit rate is decreasing in the age of the council. However, our estimates also provide evidence of a codetermination life cycle.
Keywords: J52; J53; K31; M54; 330; Codetermination; Learning; Conflict; Cooperation; Performance